Development and Validation of a Dual-Dimensional Battery for Assessing Physical and Technical Performance in Youth Volleyball Players - Amer Mishaal Faihan (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Youth volleyball players tend to be assessed separately based on their physical or technical ability without considering the interaction of physical and technical skills that are important in the performance of the players. The purpose of the proposed study was to design and calibrate a new dual-dimensional test battery, which unites physical and technical characteristics to have a comprehensive representation of performance in young players of volleyball. The important physical aspects (strength, agility, endurance, and reaction time) and technical aspects (serving accuracy, spiking velocity, passing precision) were identified as the key issues in the design phase based upon literature review and consultation with experts in the field. To test feasibility, internal consistency, and test-retest reliability in the form of first Model, a cohort of young volleyball players (n = 30) was pilot-tested through Cronbach alpha (Cronbach) and intraclass correlation coefficients (ICC) method. To test construct validity during the validation phase, the results were compared to the corresponding and reputable standardized performance tests, and content validity was provided by experts/certified coaches. The statistical methods used were exploratory factor analysis and confirmatory factor analysis to support the two-dimensional structure of the battery and regression analysis models to investigate physical and technical scores as the predictors of in-game performance measures. These results revealed that the instrument to be widely used has a good internal consistency, high inter-rater reliability, and notable predictive validity, which confirms that the battery is reliable, comprehensive, and practical as an instrument to assess the youth volleyball players. It is a two-dimensional methodology which has the potential of facilitating talent identification, training optimization and performance monitoring of volleyball development programs